Correlation between Cardiac Ultrasound Index and Cardiovascular Risk in Healthy Obese and Overweight Populations - Xiaoyu Pan; Xiaoyi Chen; Lin Ren; Zelin Li; Shuchun Chen (International Journal of Clinical Practice)
Objective. To investigate the correlation of obesity and overweight with cardiac ultrasound parameters and future cardiovascular risk among healthy populations. Methods. Basic clinical characteristics as well as cardiac ultrasound parameters were collected from healthy people. Firstly, all participants were divided into three groups: normal, overweight, and obese. Then the differences in cardiac ultrasound parameters between the three groups were calculated. Subsequently, those aged 35–60 years were screened to determine their cardiovascular risk according to the SCORE system. Finally, the correlation between cardiac ultrasound indices and cardiovascular risk was calculated. Results. A total of 1328 healthy participants were included, of whom 504 were normal, 580 were overweight and 244 were obese. Obesity and overweight significantly increased the aorta, left atrium, right atrium, right ventricle, the end-diastolic diameter of the left ventricle, main pulmonary artery, right ventricular outflow tract, interventricular septum, left ventricular posterior wall, and triglycerides and decreased E/A values and high-density lipoprotein-cholesterol. Ejection fraction, fractional shortening, low-density lipoprotein-cholesterol, and total cholesterol did not change between the three groups. A total of 781 participants were screened for SCORE scores. Obesity and being overweight significantly increased the incidence of future cardiovascular events, and lower E/A values were also associated with cardiovascular risk. All cardiac parameters were strongly associated with cardiovascular risk. Conclusion. Our research demonstrates that obesity and overweight can damage heart shape and function and raise the risk of future cardiovascular events in people that are healthy. Cardiovascular risk and cardiac structural and functional impairments are significantly positively correlated.